PENERAPAN MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA BIOLOGI - Yentri Nitatistik Nehe (TUNAS : Jurnal Pendidikan Biologi, 2023)
The purpose of this study is to describe the increase in student motivation and increase student learning outcomes through the student facilitator and explain learning model. The research method used is a classroom action research method which is carried out in two cycles. This classroom action research was carried out in four stages, namely: planning, implementing action, observing, and reflecting. Based on the research, the students' learning outcomes in the first cycle were 64.84 with learning completeness of 56.25%. After reflection in the first cycle, the implementation of the second cycle so that there is an increase in learning outcomes of 82.5 with learning mastery reaching 90.62% based on learning outcomes in cycle I and cycle II it can be said that the learning model is facilitator and student explanation. Can improve student learning outcomes. In line with the conclusions above, the suggestions of this research are: (1) for Biology science subject teachers to apply the student facilitator learning model and explain in order to improve students' abilities because it can make students active and build cooperative nature, (2) for readers who wish to research further, in order to improve learning methods by generating new ideas so that the student facilitator learning model and explaining can get better results than before.